2010
DOI: 10.1111/j.1365-2095.2009.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary menadione nicotinamide bisulphite (vitamin K3) and phylloquinone (vitamin K1) on Atlantic salmon (Salmo salar L.) tissue levels, determined by high-performance liquid chromatography with fluorescence detection

Abstract: The aim of the present study was to investigate the retention of menadione nicotinamide bisulphite (MNB; vitamin K3) and phylloquinone (vitamin K1) in Atlantic salmon (Salmo salar L.). Another objective was to find a reliable method for determination of menadione in fish feed, and to include and validate more matrices in the methods for phylloquinone and menaquinones (vitamin K2). Duplicate tanks of Atlantic salmon (∼93 g) were fed four levels (0–1000 mg menadione kg−1 feed) of MNB for 9 weeks. The concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…It is not itself biologically active and is easily excreted, but can at least be partly alkylated enzymatically to MK‐4 in tissues when present in animal feeds (Dialameh et al. 1971; Udagawa 2000; Graff et al. 2002, 2010; Okano et al.…”
Section: Chemistry and Function Of Vitamin Kmentioning
confidence: 99%
“…It is not itself biologically active and is easily excreted, but can at least be partly alkylated enzymatically to MK‐4 in tissues when present in animal feeds (Dialameh et al. 1971; Udagawa 2000; Graff et al. 2002, 2010; Okano et al.…”
Section: Chemistry and Function Of Vitamin Kmentioning
confidence: 99%
“…This is in agreement with earlier studies by Sadowski et al (1976) and Buitenhuis et al (1990), which demonstrated that only vitamin K 1 and K 2 can work as a cofactor for GGCX. In farmed Atlantic salmon fed a standard commercial diet, Graff et al (2009) found *70 lg MK-4 kg -1 in heart, 45 lg MK-4 kg -1 in kidney and 30 lg MK-4 kg -1 in both liver and muscle. However, our results showed more than a two-fold higher activity of GGCX in liver compared to muscle.…”
Section: Discussionmentioning
confidence: 98%
“…However, Graff et al (2010) added increasing amounts of MNB to salmon diets (10, 100 and 1 000 mg menadione/kg feed), which was produced according to commercial manufacturing procedures, and found recovery of only 3-5 % two months after production.…”
Section: Stability and Homogeneitymentioning
confidence: 99%
“…The real requirements may therefore be considerably lower. They require at least a new assessment (Graff et al, 2010).…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
See 1 more Smart Citation